A formação inicial de professores de Física e a interdisciplinaridade: a partir de discussões do fazer interdisciplinar à práxis interdisciplinar - Dameão, Ana Paula (2023)
This research was conducted within the Postgraduate Program in Science Teaching (PPEC) at Doctoral level, affiliated with the Federal University of Mato Grosso do Sul (UFMS). The object of study for this work was interdisciplinarity. We began with the hypothesis that teachers lack a clear understanding of interdisciplinarity and the praxis necessary for the development of themselves as interdisciplinary beings and, subsequently, of attitudes that lead to interdisciplinary teaching in an academic and/or school environment. In this context, the central question is: “How is interdisciplinarity being developed in the initial training of teachers, based on the adaptation of pedagogical projects of undergraduate courses in Physics in the Central West region, in light of Resolution CNE/CP 02/2015?” To address this question, we drew upon the theoretical frameworks provided by the following authors: Fazenda, Fourez, Freire and Vásquez. In this research, we carried out through documentary research, an analysis of Resolution CNE/CP 2/2015 and the Pedagogical Projects of the Physics Courses (PPC) Degree programs at Public Higher Education Institutions in the Central-West region, seeking to understand how interdisciplinarity, as proposed by Resolution CNE/CP 02/2015, is being developed in the initial training of Physics teachers in Physics Degree courses at the chosen HEIs. The research participants were six professors from HEIs in the Central-West who have their PPC from the current Physics Degree course, in accordance with Resolution CNE/CP 02/2015. To carry out the investigation, a qualitative approach was adopted, utilizing methodologies such as Conversation Circles for data production and some principles of Collaborative Research for data analysis. During data analysis, the following thematic axes were identified: Concept of Interdisciplinarity, a priori, The Influence of Disciplinarity, Interdisciplinary Teaching Attitude, Subjectivity of Interdisciplinarity: Doing, working, teaching and being, and, finally, Interdisciplinarity: from intentionality to interdisciplinary praxis, a posteriori. These thematic axes highlighted how the polysemous nature of the term interdisciplinarity leads to various interpretations of what interdisciplinarity is and its interdisciplinary practice. We considered the aspects of working, teaching and being interdisciplinary as a whole. Therefore, it was possible to observe, through sharing and reports of experiences, the academic and professional path of the participating teachers; their understanding of the term interdisciplinarity; how interdisciplinarity has been developed in academic settings and the possibilities for developing interdisciplinarity in the HEIs in which they work. We identified that interdisciplinarity cannot be achieved without disciplinarity and that collaborative work is not present in the speeches of the participating teachers as a tool to provide interdisciplinary praxis. As a result, we found uncertainty regarding the definition of interdisciplinarity and interdisciplinary practice, especially interdisciplinary praxis.